2013
DOI: 10.1002/hep.26047
|View full text |Cite
|
Sign up to set email alerts
|

Wilson's disease: Changes in methionine metabolism and inflammation affect global DNA methylation in early liver disease

Abstract: Hepatic methionine metabolism may play an essential role in regulating methylation status and liver injury in Wilson disease (WD) through the inhibition of S-adenosylhomocysteine hydrolase (SAHH) by copper (Cu) and the consequent accumulation of S-adenosylhomocysteine (SAH). We studied the transcript levels of selected genes related to liver injury, levels of SAHH, SAH, DNA methyltransferases genes (Dnmt1, Dnmt3a, Dnmt3b) and global DNA methylation in the tx-j mouse (tx-j), an animal model of WD. Findings were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
89
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 44 publications
14
89
1
1
Order By: Relevance
“…On the other hand, there is a large body of literature demonstrating profound DNA methylation alterations in liver pathology. For instance, global DNA hypo-methylation has been reported in liver injury induced by Wilson's disease (Medici et al, 2012), as well as in liver cells following treatment with triclosan, which is thought to cause liver tumors (Ma et al, 2013). Furthermore, it has been shown that hypo-methylation plays a crucial role in the onset of liver fibrosis and the progression of the disease to cancer (Komatsu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is a large body of literature demonstrating profound DNA methylation alterations in liver pathology. For instance, global DNA hypo-methylation has been reported in liver injury induced by Wilson's disease (Medici et al, 2012), as well as in liver cells following treatment with triclosan, which is thought to cause liver tumors (Ma et al, 2013). Furthermore, it has been shown that hypo-methylation plays a crucial role in the onset of liver fibrosis and the progression of the disease to cancer (Komatsu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this model, the methylation level was increased by copper chelation or by treatment with a methyl group donor. This suggested that Wilson's disease is a condition associated with an increased demand for methyl groups due to an increase in the levels of the methylation inhibitor SAH, which is attributable to an inhibitory effect of copper on SAHH [62]. The association between oxidative stress and hypomethylation of LINE-1 sequences was reported in bladder cancer patients [63].…”
Section: Induction Of Epigenetic Instability By Oxidative Stressmentioning
confidence: 99%
“…An increase in inflammation in the liver tissue with reduced SAH hydrolase (SAHH) activity, and increased liver SAH, which could also cause global DNA hypomethylation [62], was observed in a mouse model of Wilson's disease. In this model, the methylation level was increased by copper chelation or by treatment with a methyl group donor.…”
Section: Induction Of Epigenetic Instability By Oxidative Stressmentioning
confidence: 99%
“…The level of methylation was found to decrease with age (Mazin et al 1985;Vanyushin 2005). Other authors confirmed these reports in the case of organs of cattle, mice, and rats (Bird 2002;Medici et al 2013). The importance of DNA methylation for the development of the organism is demonstrated by the fact that mice lacking the DNA methyltransferase gene die within 8 d of fertilization (Sulewska et al 2007;Couldrey and Wells 2013).…”
Section: Discussionmentioning
confidence: 89%